Evaluating “Cultural Translation” and Intermodal Address in the Musée du quai Branly's Exhibition of African Material Objects - Celis, Abigail (TTR, 2019)
The debate on what cultural translation as an analytical and political tool can offer has sparked much discussion in translation studies as well as in the fields of anthropology, literature, and cultural studies. To a lesser degree, some museum studies scholars have likewise evoked the notion of translation to address the ethics of representing culture in and across differences. This article expands on these discussions by evaluating whether a translational lens can serve to rethink the display of African material culture in museums. Through an analysis of the textual, spatial, and visual elements of the permanent African exhibition at the Musée du quai Branly-Jacques Chirac (MQB) in Paris, France, I argue that though the MQB claims that it seeks to foster cultural dialogue, the “translations” of its African collection tend to reproduce the museum’s norms of meaning-making, rather than the norms of the non-European cultures it presents. However, I also suggest that by approaching its task as one of multimodal translation, the MQB could reshape its museographic language to reflect ways of making meaning that are more evenly in dialogue with ways of making meaning from the objects’ contexts of origin.